De-duplication of aggregation authority files. (25th October 2012) - Manghi, P.; Mikulicic, M.; Atzori, C.
This paper presents PACE (Programmable Authority Control Engine), an authority control tool conceived to maintain 'aggregation authority files'. These are obtained as continuous aggregations of records originating from a variable set of information systems with heterogeneous and duplicated content. To facilitate record deduplication in the presence of such heterogeneity and dynamicity, PACE user interfaces enable an iterative curation process, where data curators can: (i) confi gure algorithms for the identification of record duplicates; (ii) open work sessions where algorithm configurations can be run and evaluated; (iii) merge the identified record duplicates to disambiguate the authority fi le and ( iv ) repeat this cycle several times. PACE supports a tunable probabilistic similarity measure and performs record matching with a customisable variation of the sorted neighbourhood heuristic. Finally, it addresses the underlying performance and scalability issues by exploiting multi-core parallel processing and Cassandra's storage systems, to support I/O performances that scale up linearly with the number of records.